Dysregulation of PER3 clock gene and its only pseudogene in colorectal cancer and type 2 diabetes - Najari-Hanjani, Parisa; Najafi, Rana; Akbar, Sorush (Archives of Biological Sciences, 2022)
Paper description: The period (PER) family gene PER3P1 is the only known pseudogene of the circadian clock. The expression patterns of PER3P1 in Iranian patients with colorectal cancer (CRC) and type 2 diabetes (T2D) were examined. PER1/2/3 genes and the PER3P1 pseudogene are significantly downregulated in CRC. PER3 and PER3P1 mRNAs are significantly upregulated in T2D. PER3P1 pseudogene and could serve as a potential diagnostic biomarker in CRC and T2D. Abstract: The period (PER) family genes (PER1, PER2, and PER3) play a fundamental role in regulating the day/night cycle. PER3 has a pseudogene variant, PER3P1 or PER4, whose role and expression pattern is unclear in human health and diseases. This study was performed to evaluate the expression levels of normal PER family members and the PER3P1 pseudogene in colorectal cancer (CRC) and type 2 diabetes (T2D). Blood samples were taken from 50 diabetic patients and analyzed using real-time PCR for quantification of PER3 and PER3P1 expression. Colorectal tumor tissues of 50 individuals were also used to evaluate the expression of PER members. All PER members, including PER3P1, were found to be downregulated in colorectal tumor samples. Blood samples collected from diabetic subjects revealed an opposite expression pattern; both PER3 and its pseudogene were found to be upregulated when compared to the control group. Our results reveal coordination between the expression pattern of PER3P1 and normal PER family genes. Based on our findings and the pathological importance of this pseudogene, it can be suggested that PER3P1 may be one of the key regulators of the molecular clock network and PER family expression. This hypothesis needs to be confirmed by further studies.